The impact of production shocks on maize markets in Ethiopia: Implications for regional trade and food security - Mesay Yami; Ferdinand Meyer; Rashid M. Hassan (Agricultural and Food Economics, 2020)
In this article, we demonstrated the dynamic impact of a bumper harvest and drought shocks on the maize market and on the trade regime in Ethiopia. Regional market integration of Ethiopia's white maize market with the South Sudan and Kenyan maize markets was also examined using cointegration analysis. Despite the renewed conflict in South Sudan, Addis Ababa maize market is cointegrated with Juba's maize market. The simulation analysis indicated that a 20% increase in maize yield could reduce the maize price by 81%. This implies a decrease in the maize price level of 70% (110 USD/t) below the export parity price. This makes maize exports profitable and shifts the trade regime from autarky to an export parity regime. On the other hand, the effect of a drought could increase maize prices by 61% in the short run (within the year). At the current market price, the domestic maize price is wandering between the border prices and it is unprofitable to export maize. Therefore, lifting the export ban, even during normal harvest seasons, would not do any harm to the domestic maize price.
Keywords: 330; Export bans; Maize; Price stabilization; Production shocks; Traders